Milk production and processing - Griffiths, Mansel W. (Woodhead Publishing in food science, technology, and nutrition ;, 2010)
Consumers demand quality milk with a reasonable shelf-life, a requirement that can be met more successfully by the milk industry through use of improved processes and technologies. Guaranteeing the production of safe milk also remains of paramount importance. Improving the safety and quality of milk provides a comprehensive and timely reference to best practice and research advances in these areas. Volume 1 focuses on milk production and processing. Volume 2 covers the sensory and nutritional quality of cow's milk and addresses quality improvement of a range of other milk-based products. The opening section of Volume 1: Milk production and processing introduces milk biochemistry and raw milk microbiology. Part two then reviews major milk contaminants, such as bacterial pathogens, pesticides and veterinary residues. The significance of milk production on the farm for product quality and safety is the focus of Part three. Chapters cover the effects of cows' diet and mastitis, among other topics. Part four then reviews the state-of-the-art in milk processing. Improving the quality of pasteurised milk and UHT milk and novel non-thermal processing methods are among the subjects treated. With its distinguished editor and international team of contributors, volume 1 of Improving the safety and quality of milk is an essential reference for researchers and those in industry responsible for milk safety and quality. Addresses consumer demand for improved processes and technologies in the production, safety and quality of milk and milk productsReviews the major milk contaminants including bacterial pathogens, pesticides and vetinary residues as well as the routes of contamination, analytical techniques and methods of controlExamines the latest advances in milk processing methods to improve the quality and safety of milk such as modelling heat processing, removal of bacteria and microfiltration techniques.